2010
DOI: 10.1089/scd.2009.0326
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Pluripotency of Human Embryonic Stem Cells Maintained on Type I Collagen

Abstract: Human embryonic stem cells (hESC) require a balance of growth factors and signaling molecules to proliferate and retain pluripotency. Conditioned medium (CM) from a human embryonic germ-cell-derived cell culture, SDEC, was observed to support the growth of hESC on type I collagen (COL I) and on Matrigel (MAT) biomatricies. After 1 month, the population doubling of hESC grown in SDEC CM on COL I was equivalent to that of hESC grown in mouse embryonic fibroblast (MEF) CM on MAT. hESC grown in SDEC CM on COL I ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 94 publications
(129 reference statements)
1
12
0
1
Order By: Relevance
“…The key factor in terms of multipotency and self-renewal characteristics of stem cells is the control by the expression of several unique multipotency-associated marker genes as for example, KLF4, cMYC, SOX2, HMGA2, and OCT4 [1316, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…The key factor in terms of multipotency and self-renewal characteristics of stem cells is the control by the expression of several unique multipotency-associated marker genes as for example, KLF4, cMYC, SOX2, HMGA2, and OCT4 [1316, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence of a strong connection between ECM and maintenance of stem cell characteristics. Another study reported that ECSs maintained in the presence of collagen I have superior proliferation rates and pluripotency potential (Jones et al, 2010). Moreover, the present results show that collagen I (10 µg/ml) maintained the mESCs in an undifferentiated state in the presence of LIF.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to utilize two different families of ECM proteins (fibrillar Col I and reticular Laminin) to establish proof of concept. In addition, we selected these two molecules as they have both been included in protocols designated either to enhance stem cell growth 61,62 or to encourage stem cell differentiation to cardiomyocytes, 6366 which is of particular interest for our laboratory. Previously, we reported that Col I and Laminin are two of the primary constituents of the developing myocardium.…”
Section: Discussionmentioning
confidence: 99%